2017
DOI: 10.1177/1077801217741219
|View full text |Cite
|
Sign up to set email alerts
|

Bar Training for Active Bystanders: Evaluation of a Community-Based Bystander Intervention Program

Abstract: Bystander intervention programs are proliferating on college campuses and are slowly gaining momentum as sexual violence prevention programs suitable for the larger community. In particular, bystander intervention programs aimed at bar staff have been developed in a number of locations. This study entails the exploratory evaluation of a community-based bystander program for bar staff. Using a pre-posttest design, this study suggests that evidence surrounding the effectiveness of this program is promising as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 50 publications
5
44
1
3
Order By: Relevance
“…If alcohol negatively influences risk detection, increasing the presence of trained bystanders who are not intoxicated could facilitate the likelihood of effective bystander intervention. This may be accomplished by encouraging identification of designated "sober" friends when planning a night out, or by training individuals employed in settings in which alcoholrelated sexual violence is common to be effective bystanders (e.g., bartenders; Powers & Leili, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…If alcohol negatively influences risk detection, increasing the presence of trained bystanders who are not intoxicated could facilitate the likelihood of effective bystander intervention. This may be accomplished by encouraging identification of designated "sober" friends when planning a night out, or by training individuals employed in settings in which alcoholrelated sexual violence is common to be effective bystanders (e.g., bartenders; Powers & Leili, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it will be important for us to be innovative in where we implement sexual violence prevention programs to affect campus climate and reduce victimization. For example, studies have evaluated the effectiveness of bystander intervention programs among bar staff, showing promise of these programs in reducing rape myth acceptance and increasing bartenders’ willingness to intervene if they witness abusive behavior in these off-campus settings (Powers & Leili, 2018). Doing this work from an intersectional, community-engaged perspective would strengthen our ability to acknowledge the collective and historical trauma of a community, especially communities of color, to promote trauma-informed practice on and off campuses.…”
Section: For the Future: Applying An Intersectional Community-engagementioning
confidence: 99%
“…Despite low rates of aggression in bars overall, the program proved to be somewhat effective in reducing incidents of severe and moderate aggression (Graham et al., ). In similar fashion, Powers and Lelli () describe the evaluation of a community‐based bystander intervention program for bar staff delivered in the workplace. Initial evaluation suggested that the intervention program led to a decrease in rape myths, a reduction in barriers to intervention, and an increase in bartenders’ willingness to intervene.…”
Section: Rethinking the Bystander Effect In Violence Reduction Programsmentioning
confidence: 99%